2021
DOI: 10.3168/jds.2020-19979
|View full text |Cite
|
Sign up to set email alerts
|

Synbiotic sheep milk ice cream reduces chemically induced mouse colon carcinogenesis

Abstract: Sheep dairy products containing prebiotic and probiotic ingredients may have health-promoting properties. Thus, this study evaluated the effects of sheep milk ice cream [conventional full-fat (CONV), full-fat enriched with probiotic (PROB, 100 mg % wt/wt of Lacticaseibacillus casei 01), or nonfat synbiotic (SYNB, Lacticaseibacillus casei 01 and inulin, 10% wt/wt)] on carcinogen-induced colonic crypt cytotoxicity and premalignant lesion development. Male Swiss mice received 2 doses of colon carcinogen azoxymeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 46 publications
1
28
0
1
Order By: Relevance
“…In addition, panobinostat increases nuclear histone and non-histone acetylation, thus regulating gene expression and protein activity associated with cancer cell growth and survival pathway (Crisanti et al, 2009). GSK126, as an EZH2 selective inhibitor, is closely related to the occurrence and development of tumors (Zeng et al, 2017;Balthazar et al, 2021). Our results showed that azacytidine, panobinostat and GSK126 respectively inhibited cell viability and invasion in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, panobinostat increases nuclear histone and non-histone acetylation, thus regulating gene expression and protein activity associated with cancer cell growth and survival pathway (Crisanti et al, 2009). GSK126, as an EZH2 selective inhibitor, is closely related to the occurrence and development of tumors (Zeng et al, 2017;Balthazar et al, 2021). Our results showed that azacytidine, panobinostat and GSK126 respectively inhibited cell viability and invasion in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 61%
“…The majority of family members harbor various biological functions, including promoting cell proliferation and differentiation, inhibiting cell apoptosis and intercellular interactions, which exert regulatory effects on critical biological and pathological process (Hashimoto et al, 2019;Ismail et al, 2020;Li et al, 2020;Negrão et al, 2021). The migration, proliferation and differentiation of lumen morphology would lead to the angiogenesis of tumor (Balthazar et al, 2021;Hu et al, 2021;Khan et al, 2021). Recent studies have demonstrated that CLDN18, a member of CLDN family, is involved in regulation of angiogenesis of tumor, playing a vital role in the tumorigenesis and metastasis (Coati et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…can contribute to the reduction of postprandial glycemia in healthy individuals. Balthazar et al (2021a) indicated that L.casei (especially with inulin), can reduce chemically induced mouse colon carcinogenesis. Vasconcelos et al (2019) suggested that some probiotic lactobacillus strain was reduced oxidative stress in the liver lungs, and gut.…”
Section: Introductionmentioning
confidence: 99%